(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Ethanolic extracts of pneumatophores of two mangrove species- Avicennia alba and Sonneratia apetala were studied in vitro for antioxidant capacity by measuring their ability to scavenge free radicals and determining total phenolic, flavonoid and tannin contents. In vivo measurement of antihyperglycemic activity of extracts was done by oral glucose tolerance test. In considering the antioxidant activity, S. apetala extract showed superior IC50 (concentration of sample required to inhibit 50% of free radicals) value for scavenging DPPH radical (71.77 μg/ml), hydrogen peroxide radical (97.27 mg/l), hydroxyl radical (79.62 mg/l) and superoxide anion (108.89 mg/l). For A. alba, the values for the radical scavenging assays were much higher. In addition, total phenol, flavonoid and tannin content demonstrated by S. apetala were 204.03 mgGAE/g, 228.68 mgQE/g and 235.89 mgGAE/g whereas for A. alba, they were 65.52 mgGAE/g, 44 mgQE/g and 37.71 mgGAE/g, respectively. In oral glucose tolerance test, S. apetala reduced the blood glucose level to a higher extent than A. alba. So, S. apetala with higher amount of secondary metabolites (phenol, flavonoid, tannin) is a superior source of natural antioxidants and antihyperglycemics. Dhaka Univ. J. Pharm. Sci. 17(2): 205-211, 2018 (December)